Reconstructing Islamic Bioethics as A Lakatosian Research Programme - Fikri, Muhammad Dhiaul; Amrulloh, Muhamad Wildan Arif; Mulyana, Ana (Millati: Journal of Islamic Studies and Humanities, 2026)
Contemporary Islamic bioethics has largely evolved through case-based juridical responses, resulting in perceptions of fragmentation and limited theoretical integration within the global bioethical discourse. This article addresses the epistemic gap underlying this condition by proposing a structural reconstruction of Islamic bioethics, inspired by Imre Lakatos’s Methodology of Scientific Research Programs (MSRP). The study aims to demonstrate how Islamic bioethics can be conceptualized not merely as a collection of fatwas, but also as a coherent normative research program with an identifiable theoretical core and adaptive methodological mechanisms. Through normative-philosophical and conceptual analyses grounded in Islamic legal theory and the philosophy of science, the paper maps key components of Islamic ethical reasoning onto categories derived from Lakatos. Findings indicate that Islamic bioethics maintains a stable hard core rooted in theological-ontological commitments such as the sanctity of life and the prohibition of harm, while tools of ijtihād, including maqāṣid al-sharīʿah, legal maxims, and doctrines of necessity, serve as a dynamic protective belt. Furthermore, the structure of ḍarūriyyāt al-khams functions heuristically in both affirmative (wujūdan) and preventive (ʿadaman) modes, guiding ethical innovation while safeguarding foundational commitments. This reconstruction repositions Islamic bioethics as a progressive normative program capable of systematic development, thereby enhancing its methodological legitimacy and fostering a more balanced engagement with global bioethical frameworks, without compromising its normative identity.